Analysis of naturally etched surface of brass sheathing from a nineteenth-century shipwreck - Ashkenazi, Dana; Inberg, A.; Cvikel, D. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The Akko Tower Wreck is apparently the remains of a 25-m-long merchant brig, dated to the first half of the nineteenth century. During the 2015 underwater excavation, a piece of brass sheet was retrieved from the shipwreck and its surface and bulk were examined by metallurgical analyses. The examinations revealed a unique example of almost two hundred years’ natural etching, which took place in the sea underwater environment. The surface of the sheet was covered with different copper and zinc oxides, which were identified by XRD analysis. Observation of the naturally etched surface with multi-focal light microscopy and SEM-EDS analysis indicated a microstructure of annealed alpha-brass, similar to that of its bulk. S-OES chemical analysis of the bulk revealed a composition of 65.0 wt% Cu, 34.4 wt% Zn and 0.6 wt% Pb. Based on the thickness of the sheet and its good state of preservation, it is suggested that it was used as sheathing to protect the hull against marine organisms, and to improve the sailing qualities of the ship. The results provide further information about the Akko Tower shipwreck; and expand our knowledge regarding the corrosion processes and preservation of brass during a long burial period in marine environments.